How Can Meaning in Life be Reached by Mothers of Children with Special Needs? - Aziz, Rahmat; Mangestuti, Retno (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS)DO - 10.18860/iconetos.v1i1.1149, 2020)
The study of meaning in life is exciting and valuable to do because everyone always craves meaning in his life. This study aims to test the effect of patience and gratitude to meaning in life. Data were taken from 100 mothers who have children with a special need. Data was obtained through The Meaningful in Life Questionnaire (MLQ), The Patience Scale and The Gratitude, Resentment, and Appreciation Test (GRAT). Data were analysed through regression analysis techniques. The results for the analysis showed that patients and gratitude influenced meaning in life both in search for meaning and presence in meaning, but for partial analysis showed that patients effect only to search for meaning, and gratitude effect only for presence in meaning. The implication is that patience and gratitude are essential as a foundation in reaching meaning in life.